The Cenozoic of the Paris basin : a high resolution sedimentary record of lithospheric deformation in low subsidence context - Briais, Justine (CCSD, 2015)
The Paris basin is currently considered as a typical example of intracratonic basin (sag) affected by long term thermal subsidence. The Cenozoic is a period a low subsidence (less than 300m thick) and correspond to the end of the Paris basin sedimentation. Moreover, it is a period of strong deformation of the European plate related to Africa Europe convergence and North Atlantic opening, well known through numerous grabens inversions in northern and eastern Europe. While hiatus have been highlighted within Paris Basin sedimentation, cenozoic deformations of this thicker crust basin still poorly known. This thesis aims at recompose high resolution temporal and spatial evolution of 3D sedimentary geometries and palaeogeographies from Thanetian to Lower Oligocene. This work is firstly based on available and newly acquired biostratigraphic data. Facies sedimentolgy and well data correlations based on sequence stratigraphy principles allowed to recompose the basin evolution at 1Ma timescale. 2 orders of sequences were identified. Third order sequences (1My duration) seems to be controlled by climate-eustasy. Five main (2nd order) sequences bounded by unconformities and/or palaeogeographic reorganization are highlighted : (1) Maastrichtian-Danian (2) Thanetian-Ypresian (3) Lutetian-Bartonian (4) Bartonian-top Priabonian et (5) Top Priabonian-Chattian. Sequences 1 to 4 correspond to basin scale flexure which control their architecture. Following emersion during the main flexural phases, flooding start with relatively steep depositional profiles. As flexure progressively relax, flatter depositional profiles take place together with overall transgression. This work yield high resolution constraints for the understanding and thermomechanical modelling of intraplate deformations various lenght of flexures form 150 to 300km and more are identified and traduces different thickness of deformed lithosphere. From Thanetian to Bartonian, successives E-W oriented flexures take place which ages are congruent with the main ...